The Influence of Supervisory Board Function, Human Resources Quality and the Utilization of Information Technology on the Quality of Financial Reports in Denpasar Village Credit Institutions - Ni Putu Mariani; Ni Wayan Yuniasih; Ni Putu Yeni Yuliantari (UNHI Press, 2023)
Purpose – This study intends to determine the function of the supervisory board, the quality of human resources and the use of information technology on the quality of financial reports. Quality financial reports are very important for LPDs to be able to assist in making decisions regarding their operations. Methodology – The population in this study were 175 employees in 35 LPDs in Denpasar City, consisting of the LPD Chair, Secretary, and Supervisory Board. The sampling technique used in this study is the saturated sampling method. Findings – The results showed that the variables of the function of the supervisory board, the quality of human resources and the use of information technology had a significant positive effect on the quality.